Fitonematoides na cultura da soja: levantamento, caracterização de espécies e reação de cultivares a Meloidogyne spp. - Kirsch, Vanessa Graciela (2016)
The soybean crop is among the crops that are most affected by the presence of nematodes, it is observed large losses in productivity each year. In view of this problem, this study aimed characterize and identify populations of nematodes present in soybean crops in the North, Northwest and South of the Rio Grande do Sul, with greater emphasis on Meloidogyne and Helicotylenchus genres, and evaluate the reaction of soybean cultivars to M. javanica, M. arenaria and M. morocciensis. The populations of Meloidogyne spp. obtained were characterized chemically by esterase (Est), and populations Helicotylenchus spp. were identified by morphometry. Subsequently, evaluated in a greenhouse the reaction of six soybean cultivars to three populations of M. javanica, M. arenaria and M. morocciensis. They identified six nematode genera associated with culture, Meloidogyne, Helicotylenchus, Tylenchus, Aphelenchus, Paratylenchus and Pratylenchus, it is identified 19 populations of Meloidogyne, comprising three species, M. javanica Est J3 (59%), M. arenaria Est A2 (12,5%) and M. morocciensis Est A3 (6,2%), and nineteen populations Helicotylenchus, comprising species H. dihystera (78%), H. multicinctus (11%) and H. pseudorobustus (11%). In assessing the reaction of soybean cultivars, BMX Ponta, BMX Potência RR, FPS Urano RR, BMX Turbo RR, TEC 6029 IPRO and Fundacep 58 RR, the populations of Meloidogyne it was found that the vegetative parameters plant height, number of branches, number of vegetables, chlorophyll content and fresh weight and shoot dry were not affected by the nematode presence. Among the cultivars tested most it was susceptible to nematode galls, regardless of the population of origin, as presented reproduction factor greater than 1 and galls index greater than 2. The cultivars BMX Ponta, BMX Potência RR, FPS Urano RR, TEC 6029 IPRO and Fundacep 58 RR were susceptible to all populations tested. The cultivar BMX Turbo RR showed resistance reaction ace populations of M. arenaria and M. morocciensis being, but susceptible populations of M. javanica.